Circular polarized microstrip antenna for wireless body area networks - Mat Nor, Zanariah (2012)
Design and construction of circular polarized (CP) microstrip antenna for Wireless Body Area Networks (WBANs) is proposed. The proposed antenna is operating at 2.4-2.4835GHz frequency. The design is etched on FR4 substrate material with a relative dielectric constant of 4.6 and thickness of 1.6mm.The single fed scheme has been used. The patch shape of the antenna is square/rectangular with truncate corner to excite two orthogonal modes with equal amplitude and in phase quadrature. L- slot is introduced to extend the bandwidth